Three dimensional nonlinear BEM formulations for the mechanical analysis of nonhomogeneous reinforced structural systems. (1st February 2021) - Neto, Antonio Rodrigues; Leonel, Edson Denner
Highlights: Three dimensional nonlinear BEM formulations for the mechanical analysis of nonhomoge-neous reinforced structural systems Antonio Rodrigues Neto and Edson Denner Leonel. Three-dimensional nonlinear formulations based on the BEM (1DBEM/BEM coupling). Reinforcement elastoplasticity behaviour. 3D viscoelastic formulation for Kelvin-Voigt and Boltzmann reinforced materials. Linear analysis of short random fibres into reinforced material via 1DBEM/BEM. Pull-out test modelling via nonlinear 1DBEM/BEM coupling formulation. Abstract: This study presents a coupling formulation for the mechanical modelling of nonhomogeneous reinforced 3D structural systems. The coupling of dissimilar reinforced materials and components provides efficient designs. Particularly, it enables high stiffness and low weight mechanical components, which are largely desired in several engineering applications. In the present study, the Boundary Element Method (BEM) mechanically represents 3D solids through elastic and viscoelastic approaches. The 1D truss BEM elements represent the reinforcements, which allow for elastoplastic behaviour. The sub-region BEM technique models the nonhomogeneous systems whereas connection 1DBEM elements allow for crossing reinforcements along materials interfaces. Bond-slip behaviour has been accounted in the formulation by a nonlinear scheme without special link elements. Different bond-slip laws can be accounted, which enables the mechanical modelling of different adherence behaviours. The proposed formulations are applied in the mechanical analysis of four complex 3D applications. The results achieved by the proposed formulations are compared against the responses of equivalent numerical methods and experimental results available in the literature. The proposed formulations lead to accurate and stable results. Besides, the applications complexity demonstrates it.